تأثير استخدام أنواع مختلفة من خامات التقوية على مظهرية التطريز الآلي - سليمان، هالة سليمان السيد (جامعة المنيا - كلية التربية النوعية, 2021)
يهدف البحث إلي التعرف على أنواع خامات التقوية التي تستخدم في التطريز الآلي والتي تعطي أعلي مظهرية للخامات المطرزة آليا - واتبع البحث المنهج الوصفي لملاءمته لتحقيق أهداف البحث - واقتصرت حدود البحث على ثلاث أنواع الخامات (حرير-ساتان-تفتاه) وخمس أنواع من التقوية، ثلاث أنواع غير منسوجة لاصقه (خفيف- متوسط- ثقيل) - ونوعين غير لاصقين (غير منسوج- كرتون (ورق مقوي) ومن أدوات الدراسة مقياس تقدير لقياس المظهرية تم عرضه علي مجموعة من المتخصصين عددهم (10) متخصصين في مجال الملابس والنسيج وتوصلت النتائج إلى أن افضل تقوية لاصقة للحرير هي التقوية الثقيلة، يليها المتوسطة ثم الخفيفة - أما بالنسبة للساتان لقد تساوت التقوية الثقيلة مع التقوية المتوسطة وأعطت افضل مظهرية. أما التفتاه فكانت التقوية الثقيلة هي اعلى مظهرية-وبالنسبة للتقوية غير اللاصقة فلقد تفوق الكرتون (الورق المقوي) على التقوية غير المنسوجة بالنسبة للثلاث خامات المستخدمة في الدراسة، وتوصي الباحثة في ضوء نتائج الدراسة الحالية بإجراء المزيد من الأبحاث المماثلة والتي تهتم بمشكلات التطريز الآلي وذلك للوصول إلى أعلى جودة للمنتجات المطرزة آليا سواء ملابس أو مفروشات.
The research aims to identify the appropriate types of interfacing materials to give the best appearance of the embroidered materials. The research followed the descriptive approach as it is suitable to achieve the objectives. The research includes three types of materials(silk-satin- taffeta) and five types of interfacing materials , three of them are non-woven adhesive (light- medium - heavy) and two of them are non-adhesive (non-woven - cardboard).One of the research tools Is a measurement scale to measure the fabric appearance. It was presented to a group of (10) specialists in the field of clothing and textiles. The study found that the best adhesive interfacing for silk is heavy interfacing followed by medium and light materials. As for satin, the heavy and medium interfacing materials were the same and gave the best results for taffeta; the heavy interfacing yielded the best result. As for non-adhesive interfacing, cardboard was better than non-woven interfacing of the three materials used in the study. In light of the results of the current study, the researcher recommends conducting more research similar to the current study, which is concerned with the problems of machine embroidery, in order to achieve the highest quality of machine embroidered products, whether clothing or upholsteries.
Keywords: صناعة المنسوجات -- تصميم الأزياء -- الخامات المطرزة -- المفروشات المنزلية